2022
DOI: 10.29244/j.agromet.36.1.51-59
|View full text |Cite
|
Sign up to set email alerts
|

Land Use Change Impact on Normalized Difference Vegetation Index, Surface Albedo, and Heat Fluxes in Jambi Province: Implications to Rainfall

Abstract: Jambi covers various land uses with different characteristics related to biogeophysical cycle. Land use plays an important role in the atmosphere-surface interaction and energy balance partition, which influenced rainfall pattern. Two proxies widely used to differentiate various land uses are albedo and normalized difference vegetation index (NDVI). However, study on albedo and NDVI relationship with rainfall in Jambi is still limited. This study aims to analyze the correlation of NDVI and albedo with rainfall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…On the contrary, farmland and forests showed the maximum and minimum contributions to LSA in winter, respectively. Azizah et al [42] investigated the effect of LULC change on NDVI, LAS, and heat fluxes, and concluded that the distribution of LSA for each LULC class from the lowest to the highest was forest, plantation, cropland, shrubs, and settlements. The distribution of NDVI was the opposite to that of LSA.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, farmland and forests showed the maximum and minimum contributions to LSA in winter, respectively. Azizah et al [42] investigated the effect of LULC change on NDVI, LAS, and heat fluxes, and concluded that the distribution of LSA for each LULC class from the lowest to the highest was forest, plantation, cropland, shrubs, and settlements. The distribution of NDVI was the opposite to that of LSA.…”
Section: Discussionmentioning
confidence: 99%